Paternal mental health during the perinatal period: A qualitative systematic review. (25th February 2020) - Shorey, Shefaly; Chan, Valerie
Abstract: Aims: To examine fathers' experiences and needs associated with mental health during the perinatal period. Design: Qualitative studies were meta‐synthesized using the steps outlined by Sandelowski and Barroso. Data sources: Six databases (PubMed, Embase, PsycINFO, CINAHL, Scopus and ProQuest) were searched for qualitative studies from each database's inception to 24 June 2019. Review methods: Studies were critically appraised using the Critical Appraisal Skills Program tool. Qualitative data were extracted, meta‐summarized, then meta‐synthesized. Results: Fourteen studies were included and four themes were identified: (a) negative feelings and psychological difficulties, (b) role strain and role conflict with multiple sources, (c) coping strategies that buffered negative feelings and psychological difficulties and (d) support needs to enhance mental health. Conclusion: Fathers reported poor mental health and expressed needs to enhance their mental health across the perinatal period. Future studies can focus specifically on paternal mental health. The development of theory‐guided, family inclusive, technology‐based healthcare services are needed to manage mental health. Healthcare providers can promote positive mental health to prepare fathers, increasing their awareness to manage their mental health and to seek timely help. Impact: Problem‐focused coping (i.e. support and problem‐solving with partners and childcare involvement) helped fathers to buffer their negative feelings and psychological difficulties. Future studies should focus on paternal mental health rather than on general fathering experiences. Healthcare providers should focus on promoting positive mental health and well‐being. Policymakers should create awareness on paternal mental health across the perinatal period. Abstract : 目的: 探讨围产期父亲心理健康相关经历与需求。 设计: 采用Sandelowski和Barroso概述的步骤进行荟萃综合定性研究。 数据来源: 通过检索六大数据库(PubMed、Embase、PsycINFO、CINAHL、Scopus和ProQuest)自建立之初到2019年6月24日期间所发表的文章进行定性研究。 评估方法: 采用批判性评估技能程序工具对本项研究进行批判性评价。提取定性数据, 并对其进行荟萃汇总与荟萃综合。 结果: 共纳入14项研究, 并确定了4项主题:(a)消极情绪和心理障碍;(b)多重来源的角色紧张和角色冲突;(c)缓解消极情绪和心理障碍的应对策略;(d)增强心理健康的支持需求。 结论: 围产期父亲心理健康状况较差, 并表示需要加强其心理健康。未来的研究可着重关注父亲的心理健康。心理健康管理需制定理论指导、家庭包容、基于技术的医疗服务。医疗保健提供者可帮助促进积极的心理健康发展, 使父亲做好准备, 提高他们管理心理健康并及时寻求帮助的意识。 影响: 聚焦于问题的应对措施(即伴侣支持和伴侣协同解决问题以及儿童保育参与)可帮助父亲缓解其消极情绪和心理障碍。今后的研究应侧重于父亲的心理健康, 而非一般的父亲经历。医疗保健提供者应注重促进发展积极的心理健康和幸福感。政策制定者应创造在围产期期间对父亲心理健康的认识。